Whatsapp assisted mathematics online learning during the covid19 pandemic using a contexual approach - Oktaviani, Rani (Pi Radian: Journal of Mathematics Education, 2023)
This study aims to describe the results of online mathematics learning using a contextual approach during the pandemic covid 19. The media used to support learning is using the whatsapp application. The subjects of this study were students of class VIII C in one of the junior high schools in West Bandung Regency, which amounts to 25 students. The data collection technique was carried out by learning using a contextual approach in accordance with the steps in which it provided a teacher observation sheet which was assessed by the observer. The method used in this study is a qualitative descriptive method. The results of theassessment of learning get a percentage (85%) with very good qualifications.